Design and Development of KURA (Number House cards) as a Numeracy Learning Medium for Early Childhood Education - Ema Putri Amalia; Tuti Firdayani; Evia Darmawani (Kumara Cendekia, 2026)
The low numeracy skills of early childhood students at TK X Palembang represent the primary issue underlying this research, with initial observations revealing that only 20% of students achieved learning mastery. This problem is triggered by the use of monotonous conventional learning media, necessitating interactive innovations such as KURA (Number House Cards). This study aims to develop KURA media that is valid and practical to improve children's counting abilities. Employing a Research and Development (R&D) method with the ADDIE model, the subjects included 20 group B students, one teacher, and three expert validators. Data were collected through observations, interviews, documentation, and questionnaire instruments, followed by descriptive percentage analysis. The results indicated that the KURA media achieved a validity rate of 93.33% (highly valid) from material, media, and language experts. Furthermore, the practicality rate reached 93% based on teacher and student responses (highly practical). In conclusion, KURA media was successfully developed as an innovative, interactive, and feasible solution to overcome numeracy challenges in early childhood through an engaging visual-manipulative approach.